?THERMAL STABILISATION OF PVC WITH JATROPHA SEED, KHAYA SEED AND RUBBER SEED OILS. EFFECT OF BARIUM AND CADMIUM SOAPS OF THE SEED OILS ON THE THERMAL DEGRADATION OF PVC - Okieimen, F E (Biological Sciences - PJSIR, 2003)
Polyvinyl chloride was mixed with barium and cadmium soaps of Jatropha seed, Khaya seed and rubber seed oils and mixtures of the metal soaps and degraded at 190°C under oxidative and nonoxidative conditions. The effectiveness of the additives in stabilizing PVC against thermal degradation was evaluated by comparing (a) the kinetic data measured at 1% conversion for the degradation of PVC in the presence of the additives with the corresponding values obtained in the absence of the additives (b) the intrinsic viscosity and level of unsaturation in the polymer samples degraded for the undergraded polymer and (c) the thermogravimetric data obtained for the degradation of PVC in the presence of the additives at a constant heating rate of 10°C min-1 up to 500°C. It was found that the additives retarded the rate of dehydrochlorination of PVC (by up to about 50% and 1% conversion) and reduced the extent of decomposition of the polymer by as much as 60%. The mixtures of the metal soaps containing more than 70%(wt) cadmium soap showed marked synergistic stabilising effect on the degradation of PVC.